The Implementation Of The 'Urf And Its Implications On The Determination Of Contemporary Sharia Economic Law - Maimun, Maimun; Kurniati, Herlina; Muflihah, Lilih (ASAS, 2022)
The study aims to apply 'urf as the tool to view the problems of contemporary shari'ah economic law and its implications on the legal determination of shari'ah economic law cases. This research used qualitative library methods which is a means of understanding and exploring the meaning of what happens to various individuals or groups, originating from humanitarian or social problems. Based on the research results, it can be concluded that business practices in the current era of free market globalization are a challenge for legal practitioners who are active in carrying out the constant ijtihad to develop thoughts on shari'ah economic law, in addition to trying to reconstruct the principles of economic law, actualize and contextualize in various contemporary shari'ah economic law issues such as transaction of buying and selling orders ('aqd bai' al-salm) through online applications; buying and selling contracts without pronouncing ṣigat al -'aqd which is done online; and others. Such practice of contract transactions has become a tradition and a necessity for the business world in this contemporary era. From here, an academic problem arises: how are shari'ah economic law and the legal istinbat process able to answer various legal cases that continue to occur? Among the alternative solutions, one of them is to apply 'urf as an ijtihad method in extracting contemporary shari'ah economic law. Keywords:, implications, the economic case of shari'ah and Application of 'urf